Coupled Effect of Curing Temperature and Moisture on THM Behavior of Cemented Paste Backfill - Wenyuan Xu; Runkang Zhao; Xiaocong Yang; Lijie Guo; Chaowu Xie; Di Wu (Advances in Civil Engineering)
Cemented paste backfill (CPB), a mixture of tailings, binder, and water, is widely and continually utilized in underground mines for subsidence control and disposal of surface hazardous waste discharge. The mechanical strength of CPB, which is the key for the backfill structure to play the role of supporting overlying roof and controlling subsidence, is governed by complex factors (thermal, hydraulic, and mechanical loads), particularly strongly affected by the environmental conditions, such as ambient temperature and humidity. Thus, it is crucial to understand and assess the response of CPB subjected to the loads mentioned above, so as to better ascertain its performance and obtain a cost-effective, safe, and stable CPB structure. Accordingly, a coupled THM model is developed to describe and analyze the performance of CPB. Comparisons between model simulation and experiment data prove the capability of the developed model in predicting the evolutions of temperature and internal relative humidity, as well as stress-strain relation of CPB. The obtained results indicate that all these properties are significantly affected by ambient humidity and temperature.